1990
DOI: 10.1111/j.1945-5100.1990.tb00981.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the existence of groups of meteorite‐producing asteroidal fragments

Abstract: Abstract-The MORP camera network in western Canada observed 56 events which we associate with meteorites larger than 0.1 kg. An additional 33 Prairie Network (central USA) fireballs with published orbits were previously identified as the sources of meteorites of at least 0.25 kg. A comparison of the MORP orbits with each other and with the PN orbits, using the D' criterion of orbital similarity, exhibits a surprising number of small values. This suggests there are groups of related objects among the 89 events.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 16 publications
1
30
0
1
Order By: Relevance
“…Additionally, we have shown that the multiple-member streams of Halliday et al (1990) found via D' clustering also do not constitute 2.5% departures from randomness; random sets of fireballs show similar frequency of such clumps. We conclude that the current level of departure from randomness in the worldwide fireball database is statistically insignificant.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Additionally, we have shown that the multiple-member streams of Halliday et al (1990) found via D' clustering also do not constitute 2.5% departures from randomness; random sets of fireballs show similar frequency of such clumps. We conclude that the current level of departure from randomness in the worldwide fireball database is statistically insignificant.…”
Section: Discussionmentioning
confidence: 94%
“…Those authors did note that the light production and fragmentation pattern of Ridgedale was quite different from that of Innisfree; they ascribed this to Innisfree having more fractures before entering the Earth's atmosphere. In a final paper, Halliday et al (1990) examined the MORP and Prairie network (McCrosky et al 1979) databases and selected several fireball groups as potentially corresponding to streams of meteoroids in Earth-crossing orbits; Innisfree/Ridgedale are part of the most significant grouping that they found, and that grouping was also proposed to be linked to a stream of asteroids by Drummond (1991).…”
Section: Innisfreementioning
confidence: 99%
See 3 more Smart Citations